2012
DOI: 10.1111/j.1365-2893.2011.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism in cyclooxygenase‐2 promoter affects hepatic inflammation and fibrosis in patients with chronic hepatitis C

Abstract: Cyclooxygenase (COX)-2 is involved in inflammation, anti-apoptosis and carcinogenesis. The -1195GG genotype of single nucleotide polymorphism (SNP) in COX-2 promoter was associated with low platelet counts in patients with chronic hepatitis C. Polymorphism of patatin-like phospholipase domain-containing protein 3 (PNPLA3) gene (rs738409 C>G) have been reported to be associated with cirrhosis, and the major genotype of SNPs near interleukin (IL)28B are related to viral clearance. The present study was designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Liver steatosis, inflammation, insulin resistance, and excessive body composition may accelerate HCC development. Among those factors, we could find none significantly associated with the SNP genotype of PNPLA3 as previously reported (Miyashita et al 2012; Kotronen et al 2009). …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Liver steatosis, inflammation, insulin resistance, and excessive body composition may accelerate HCC development. Among those factors, we could find none significantly associated with the SNP genotype of PNPLA3 as previously reported (Miyashita et al 2012; Kotronen et al 2009). …”
Section: Discussionsupporting
confidence: 79%
“…A recent genome-wide association study for Japanese patients with non-alcoholic fatty liver disease by Kawaguchi et al revealed that the risk variant of PNPLA3 148 M is significantly associated with non-alcoholic steatohepatitis, but did not show significant differences in liver steatosis or fibrosis among the patients with non-alcoholic fatty liver disease (Kawaguchi et al 2012). Miyashita et al studied the associations of the SNP genotype of PNPLA3 with liver fibrosis and inflammation for Japanese patients with chronic hepatitis C, without significant associations in the results (Miyashita et al 2012). Takeuchi et al reported that the SNP genotype of PNPLA3 might not affect HCC prognosis in Japanese patients with hepatitis B virus, HCV, or non-alcoholic fatty liver diseases (Takeuchi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PNPLA3 polymorphisms have also been reported to be associated with hepatic steatosis, fibrosis, treatment response, and carcinogenesis in CHC (Valenti et al 2011 ; Trepo et al 2011 ; Cai et al 2011 ; Valenti et al 2012 ; Clark et al 2012 ; Dunn et al 2014 ; Ezzikouri et al 2014 ; Moritou et al 2013 ; Zampino et al 2013 ; Trepo et al 2014 ; Sato et al 2013 ). However, several reports have not found an association of PNPLA3 polymorphisms with fibrosis and carcinogenesis in CHC (Trepo et al 2011 ; Nischalke et al 2011 ; Rembeck et al 2012 ; Miyashita et al 2012 ; Takeuchi et al 2013 ; Nakamura et al 2013 ; Guyot et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of COX-2 are extremely low in normal liver tissues, but up-regulated under pathological conditions such as acute liver failure (Demirel et al, 2012), hepatic fibrosis and cirrhosis (Kwon et al, 2012), as well as hepatocarcinogenesis (Giannitrapani et al, 2009). Genetic polymorphism of COX-2 has been linked with liver disease progression in human (Miyashita et al, 2012). Both clinical and animal studies demonstrate that selective inhibition of COX-2 attenuates liver dysfunctions associated with hepatic inflammation, fibrosis, cirrhosis and cancer (Planaguma et al, 2005;Breinig et al, 2007;Tu et al, 2007;Hsieh et al, 2009;Paik et al, 2009).…”
Section: Discussionmentioning
confidence: 99%